XPS flame retardant masterbatch and preparation method thereof
By using a combination method of composite flame retardant and composite adsorbent, the problem of XPS flame retardant masterbatches producing toxic gases during processing and combustion is solved, and the flame retardant, moisture-proof, anti-aging and mechanical properties of the material are improved.
Patent Information
- Application Number
- CN202510138321.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2045-02-08
AI Technical Summary
Existing XPS flame retardant masterbatches produce a large amount of toxic hydrogen bromide gas during processing and combustion, and the flame retardant has poor compatibility with polystyrene, which affects the moisture resistance, anti-aging and mechanical properties of the material.
Using a combination method of composite flame retardant and composite adsorbent, an aerogel structure is formed by coating hydroxyapatite and crosslinking antimony trioxide to improve the flame retardant effect, and hydrotalcite powder is treated through intercalation and crosslinking to form an efficient hydrogen bromide gas adsorbent.
It significantly reduces the hydrogen bromide gas production during processing and combustion of XPS flame retardant masterbatches, improves the flame retardant, moisture-proof, anti-aging and mechanical properties of the material, and reduces the smoke and thermal conductivity.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of XPS flame retardant masterbatch, and in particular to an XPS flame retardant masterbatch and a preparation method thereof. Background Art
[0002] Extruded polystyrene foam (XPS) is a new type of thermal insulation material. The preparation method of XPS is to add polystyrene particles into an extruder, inject a foaming agent into the melting section of the extruder, mix the foaming agent with the polystyrene melt, and expand and foam at the head of the extruder to form a large number of closed cells. Therefore, XPS has a closed-cell honeycomb structure, which gives XPS excellent thermal insulation, anti-aging, mechanical and moisture-proof properties. At present, XPS materials are widely used in building insulation, cold chain logistics, civil engineering, marine ships and other fields.
[0003] However, XPS materials are flammable. When exposed to fire, they will burn quickly and produce harmful gases. Therefore, in order to improve the safety of XPS materials, XPS flame retardant masterbatch is needed. As for flame retardants, the commonly used flame retardants are composed of organic flame retardants and inorganic flame retardants. Organic flame retardants mainly include halogen flame retardants, nitrogen flame retardants, and phosphorus flame retardants. Inorganic flame retardants mainly include metal hydroxide flame retardants, metal oxide flame retardants, and metal salt flame retardants. Among them, bromine flame retardants in halogen flame retardants are one of the most commonly used flame retardants at present because of their advantages of high flame retardant efficiency, small addition amount, and little impact on material properties.
[0004] The flame retardant mechanism of brominated flame retardants is that during the combustion process, brominated flame retardants can quickly decompose and release hydrogen bromide gas. Hydrogen bromide gas is densely distributed in the flame to form a protective layer, isolating the contact between oxygen and the burning material, thereby reducing the combustion rate. In addition, hydrogen bromide gas can combine with free radicals in the flame to generate stable molecules to prevent the spread of the flame. Therefore, after adding brominated flame retardants to XPS, although XPS flame retardant masterbatch with good flame retardancy can be obtained, a large amount of hydrogen bromide will be generated during the processing and combustion of XPS flame retardant masterbatch. Hydrogen bromide is a toxic gas that not only pollutes the environment, but also harms human health.
[0005] There are two common solutions to the above problems. The first solution is to add additives that can absorb hydrogen bromide gas. For example, Chinese patent CN114573920B discloses an XPS flame retardant masterbatch, preparation and application. In this patent, the XPS flame retardant masterbatch includes the following raw materials: polystyrene, composite flame retardant, acid binding agent, antioxidant, lubricant. The composite flame retardant is a mixture of methyl octabromoether and 2,3-dimethyl-2,3-diphenylbutane, and the acid binding agent is a diatomaceous earth composite material with terminal amino dendrimers grafted on the surface. The acid binding agent absorbs the hydrogen bromide gas generated during the processing and combustion of methyl octabromoether to reduce the pollution of hydrogen bromide gas to the environment and the harm to human health. However, there are two problems with the technology of this patent. The first problem is that when the acid binding agent is prepared, 3-aminopropyltrimethoxysilane is first used to modify the surface of diatomite to introduce amino groups, and then it is mixed with a polyamide-amine solution, and glutaraldehyde is added. Glutaraldehyde can cross-link the amino groups to form a cross-linked product containing amino groups with a high specific surface area on the surface of diatomite. Since the amino group is a polar group with strong hydrophilicity, it will affect the moisture-proof performance of the XPS flame retardant masterbatch. The second problem is that the acid binding agent has poor compatibility with PS, which will affect the anti-aging performance and mechanical properties of the XPS flame retardant masterbatch.
[0006] The second solution is to compound the brominated flame retardant with other flame retardants and add additives that can absorb hydrogen bromide gas. For example, Chinese patent CN116376274B discloses a brominated flame retardant reinforced nylon material and a preparation method thereof. In this patent, the brominated flame retardant reinforced nylon material includes the following raw materials: nylon resin, brominated flame retardant, antimony flame retardant, glass fiber, composite adsorbent, and processing aid. The amount of brominated flame retardant is reduced by combining the brominated flame retardant with the antimony flame retardant. The composite adsorbent is a composite of zirconium hydroxide and hydrotalcite. The composite adsorbent can absorb hydrogen bromide gas generated during the processing and combustion of the brominated flame retardant. However, after the combination of bromine flame retardant, antimony flame retardant and composite adsorbent in the patent is applied to the preparation of XPS flame retardant masterbatch, three problems arise. The first problem is that the antimony flame retardant and the composite adsorbent have poor compatibility with PS, which will affect the anti-aging and mechanical properties of the XPS flame retardant masterbatch; the second problem is that the antimony flame retardant and the composite adsorbent have poor dispersibility in PS and there is a problem of uneven dispersion. During the foaming process, it will affect the gas distribution generated by the foaming agent, further affecting the thermal insulation properties of the prepared XPS material; the third problem is that the antimony flame retardant produces a large amount of smoke during combustion, resulting in a large amount of smoke produced by the prepared XPS flame retardant masterbatch during combustion. Summary of the invention
[0007] In view of the deficiencies in the prior art, the present invention provides an XPS flame retardant masterbatch and a preparation method thereof. The prepared XPS flame retardant masterbatch has excellent flame retardant properties, generates less hydrogen bromide gas and low smoke generation during processing and combustion, and also has excellent moisture resistance, anti-aging properties, and mechanical properties. The XPS material prepared from the XPS flame retardant masterbatch of the present invention also has excellent thermal insulation properties.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing XPS flame retardant masterbatch, comprising the following steps: preparing a composite flame retardant, preparing a composite adsorbent, and granulating;
[0010] The preparation of the composite flame retardant comprises the following steps: coating hydroxyapatite, cross-linking, and primary hydrophobization;
[0011] The coated hydroxyapatite comprises adding water, anhydrous ethanol and urea into a reactor, controlling the stirring speed of the reactor to 30-60 rpm, stirring at room temperature for 10-15 min, adding sodium dihydrogen phosphate aqueous solution, stirring for 5-10 min, adding antimony trioxide, stirring for 10-20 min, adding calcium chloride aqueous solution, stirring for 10-15 min, adding sodium hydroxide to adjust the pH to 11.5-12, sealing the reactor, adding the reactor into an oven, controlling the temperature of the oven to 80-90° C., standing for 30-32 h, taking out the reactor, adding the material in the reactor into a centrifuge, controlling the speed of the centrifuge to 4000-5000 rpm, centrifuging for 10-11 min, washing the precipitate with water for 3-4 times, and vacuum drying at 85-90° C. to obtain antimony trioxide coated hydroxyapatite;
[0012] In the coated hydroxyapatite, the usage ratio of water, anhydrous ethanol, urea, sodium dihydrogen phosphate aqueous solution, antimony trioxide, and calcium chloride aqueous solution is 570-600mL: 1700-1800mL: 34-36g: 580-600mL: 100-110g: 960-1000mL;
[0013] The concentration of the sodium dihydrogen phosphate aqueous solution is 15 g / L;
[0014] The particle size of the antimony trioxide is 1 μm;
[0015] The concentration of the calcium chloride aqueous solution is 15 g / L;
[0016] The cross-linking comprises adding glacial acetic acid and the first portion of water to a reactor, controlling the stirring speed of the reactor to 30-60 rpm, stirring at room temperature for 5-10 min, adding chitosan, stirring for 15-20 min, adding antimony trioxide coated with hydroxyapatite, stirring for 1-1.5 h, adding sodium alginate, stirring for 1-1.5 h, adding the material in the reactor to a centrifuge, controlling the speed of the centrifuge to 4000-5000 rpm, centrifuging for 10-11 min, adding the obtained precipitate and the second portion of water to a reactor, controlling the stirring speed of the reactor to 30-60 rpm, stirring at room temperature for 10-15 min, dripping sodium tripolyphosphate aqueous solution, stirring for 1.5-2 h after the dripping is completed, adding the material in the reactor to a centrifuge, controlling the speed of the centrifuge to 4000-5000 rpm, centrifuging for 9-10 min, washing the precipitate with water for 3-4 times, and vacuum drying at 85-90° C. to obtain cross-linked antimony trioxide;
[0017] In the cross-linking, the usage ratio of glacial acetic acid, the first portion of water, chitosan, antimony trioxide coated with hydroxyapatite, sodium alginate, the second portion of water, and sodium tripolyphosphate aqueous solution is 13-15mL:970-1000mL:10-11g:100-110g:7-8g:340-360mL:300-320mL;
[0018] The weight average molecular weight of the chitosan is 50 kDa, and the degree of deacetylation is 90%;
[0019] The concentration of the sodium tripolyphosphate aqueous solution is 50 g / L;
[0020] The sodium tripolyphosphate aqueous solution is added at a rate of 15-20 mL / min;
[0021] The primary hydrophobization comprises adding Tween 80 and water into a reactor, controlling the stirring speed of the reactor to 30-60 rpm, stirring at room temperature for 15-20 min, adding cross-linked antimony trioxide, stirring for 1.5-2 h, adding the material in the reactor into a centrifuge, controlling the speed of the centrifuge to 4000-5000 rpm, centrifuging for 14-15 min, washing the precipitate with water for 3-4 times, and vacuum drying at 100-105° C. to obtain a composite flame retardant;
[0022] In the primary hydrophobization, the usage ratio of Tween 80, water, and cross-linked antimony trioxide is 28-30 g:750-800 mL:110-120 g;
[0023] The preparation of the composite adsorbent comprises the following steps: intercalation, secondary hydrophobization;
[0024] The intercalation comprises adding glacial acetic acid and the first portion of water into a reactor, controlling the stirring speed of the reactor to 30-60 rpm, stirring for 5-10 min at room temperature, adding chitosan and polyvinyl alcohol, stirring for 15-20 min, adding hydrotalcite, controlling the temperature of the reactor to 60-65° C., stirring for 5-6 h, adding the materials in the reactor into a centrifuge, controlling the speed of the centrifuge to 8000-9000 rpm, centrifuging for 10-11 min, and mixing the obtained precipitate with the second portion of water. Add water to the reactor, control the stirring speed of the reactor to 30-60 rpm, stir at room temperature for 10-15 min, add glutaraldehyde aqueous solution dropwise, control the temperature of the reactor to 50-55° C. after the addition is completed, stir for 3.5-4 h, add the materials in the reactor to a centrifuge, control the speed of the centrifuge to 8000-9000 rpm, centrifuge for 10-11 min, wash the precipitate with water 3-4 times, and vacuum dry at 85-90° C. to obtain intercalated hydrotalcite powder;
[0025] In the intercalation, the usage ratio of glacial acetic acid, the first portion of water, chitosan, polyvinyl alcohol, hydrotalcite, the second portion of water, and glutaraldehyde aqueous solution is 13-15 mL: 970-1000 mL: 10-11 g: 24-25 g: 30-32 g: 250-260 mL: 140-150 mL;
[0026] The particle size of the hydrotalcite is 500 nm;
[0027] The weight average molecular weight of the chitosan is 50 kDa, and the degree of deacetylation is 90%;
[0028] The specification of the polyvinyl alcohol is polyvinyl alcohol 1788;
[0029] The concentration of the glutaraldehyde aqueous solution is 5wt%;
[0030] The dropping speed of the glutaraldehyde aqueous solution is 9-10 mL / min;
[0031] The secondary hydrophobization is performed by adding Tween 80 and water into a reactor, controlling the stirring speed of the reactor to 30-60 rpm, stirring at room temperature for 15-20 min, adding the intercalated hydrotalcite powder, stirring for 1.5-2 h, adding the material in the reactor into a centrifuge, controlling the speed of the centrifuge to 8000-9000 rpm, centrifuging for 14-15 min, washing the precipitate with water for 3-4 times, and vacuum drying at 100-105° C. to obtain a composite adsorbent;
[0032] In the secondary hydrophobization, the usage ratio of Tween 80, water, and intercalated hydrotalcite is 10-11 g: 500-550 mL: 34-37 g;
[0033] In the granulation, polystyrene, methyl octabromoether, composite flame retardant, composite adsorbent, antioxidant 168, zinc stearate, and 3-aminopropyltriethoxysilane are added to a mixer and mixed evenly, and then added to a twin-screw extruder for melt extrusion to obtain XPS flame retardant masterbatch;
[0034] In the granulation, the mass ratio of polystyrene, methyl octabromoether, composite flame retardant, composite adsorbent, antioxidant 168, zinc stearate, and 3-aminopropyltriethoxysilane is 34-35:25-27:12-14:7-8:0.3-0.4:0.4-0.5:2-2.3;
[0035] For the melt extrusion, the temperature of zone 1 of the twin-screw extruder is 160-165°C, the temperature of zone 2 is 185-190°C, the temperature of zone 3 is 195-200°C, the temperature of zone 4 is 200-205°C, the temperature of zone 5 is 205-210°C, the temperature of zone 6 is 205-210°C, and the temperature of the die head is 205-210°C.
[0036] An XPS flame retardant masterbatch prepared by the aforementioned preparation method.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] (1) The preparation method of XPS flame retardant masterbatch of the present invention comprises the following steps: a composite flame retardant and a composite adsorbent are prepared respectively during the preparation process; the composite flame retardant is used in combination with methyl octabromoether, with antimony trioxide as the core, and the synergistic flame retardancy of methyl octabromoether and antimony trioxide is utilized to improve the flame retardancy effect; when preparing the composite flame retardant, hydroxyapatite is first coated on the surface of antimony trioxide, and then chitosan and sodium alginate are adsorbed on the surface thereof, and sodium tripolyphosphate is used for cross-linking, thereby forming an aerogel of hydroxyapatite, chitosan, sodium alginate and sodium tripolyphosphate on the surface of antimony trioxide; sodium tripolyphosphate can not only play the role of a cross-linking agent, but also play the role of synergistic flame retardancy; hydroxyapatite has good thermal stability, which can improve the stability of aerogel; at the same time, aerogel can also adsorb the smoke generated by antimony trioxide, reduce the smoke emission, and inhibit combustion through the thermal insulation property of aerogel; finally, a hydrophobicization is performed once, Tween 80 is used for treatment, and the hydrophilic end of Tween 80 is combined with the hydrophilic group in the aerogel, and the hydrophobic segment is outward, thereby improving the compatibility of the composite flame retardant and polystyrene; when preparing the composite adsorbent, chitosan and polyvinyl alcohol are first used to intercalate the hydrotalcite powder, and then glutaraldehyde is used for cross-linking to fix the chitosan and polyvinyl alcohol between the layers and on the surface of the hydrotalcite powder. Chitosan plays a role in providing amino groups and hydroxyl groups, and polyvinyl alcohol further plays a role in increasing the hydroxyl group, ensuring that after cross-linking with glutaraldehyde, there are still enough hydroxyl groups to combine with the hydrophilic segment of Tween 80 to achieve hydrophobicization, and after cross-linking with glutaraldehyde, the cross-linking network is connected by covalent bonds, and the mechanical strength of the cross-linking network is high. During processing and combustion, the amino groups in the cross-linking network can adsorb hydrogen bromide gas; at the same time, the aerogel in the composite flame retardant and the cross-linking network in the composite adsorbent can also promote foaming and improve thermal insulation performance;
[0039] (2) The XPS flame retardant masterbatch prepared by the present invention has excellent flame retardant properties. The combustion performance of the XPS material prepared by the XPS flame retardant masterbatch of the present invention is B1 grade, and the oxygen index is 39.0-39.7%;
[0040] (3) The XPS flame retardant masterbatch prepared by the present invention generates less hydrogen bromide gas during processing and combustion. When the XPS flame retardant masterbatch of the present invention is prepared, the maximum hydrogen bromide gas concentration at the twin-screw die head is 6.23-6.82 ppm;
[0041] (4) The XPS flame retardant masterbatch prepared by the present invention has low smoke emission, and the smoke density level of the XPS material prepared by the XPS flame retardant masterbatch of the present invention is 11.0-12.1;
[0042] (5) The XPS flame retardant masterbatch prepared by the present invention has excellent moisture-proof performance. The water absorption rate (immersion in water for 96 hours) of the XPS material prepared by the XPS flame retardant masterbatch of the present invention is 0.3-0.4%;
[0043] (6) The XPS material prepared from the XPS flame retardant masterbatch of the present invention has excellent thermal insulation performance, and the thermal conductivity is 0.027-0.029 W / (m•K);
[0044] (7) The XPS flame retardant masterbatch of the present invention has excellent mechanical properties, and the compressive strength of the XPS material prepared from the XPS flame retardant masterbatch of the present invention is 311-347 kPa;
[0045] (8) The XPS flame retardant masterbatch of the present invention has excellent anti-aging properties. The XPS material prepared from the XPS flame retardant masterbatch of the present invention is added into a xenon lamp aging box, and the atmosphere of the xenon lamp aging box is controlled to be an air atmosphere, the temperature is 65°C, and the power is 1.8 kW. After continuous irradiation for 15 days, the compression strength decrease rate is 0.72-0.81%. DETAILED DESCRIPTION
[0046] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0047] Example 1
[0048] A method for preparing XPS flame retardant masterbatch, specifically comprising:
[0049] 1. Preparation of composite flame retardant:
[0050] (1) Coating hydroxyapatite: 570 mL of water, 1700 mL of anhydrous ethanol and 34 g of urea were added to a reactor, the stirring speed of the reactor was controlled to 30 rpm, and the mixture was stirred at room temperature for 10 min. 580 mL of sodium dihydrogen phosphate aqueous solution was added, and the mixture was stirred for 5 min. 100 g of antimony trioxide was added, and the mixture was stirred for 10 min. 960 mL of calcium chloride aqueous solution was added, and the mixture was stirred for 10 min. Sodium hydroxide was added to adjust the pH to 11.5. After the reactor was sealed, the reactor was placed in an oven, the temperature of the oven was controlled to 80° C., and the mixture was allowed to stand for 30 h. The reactor was taken out, and the contents of the reactor were placed in a centrifuge, the speed of the centrifuge was controlled to 4000 rpm, and the mixture was centrifuged for 10 min. The precipitate was washed with water for 3 times, and vacuum dried at 85° C. to obtain antimony trioxide coated with hydroxyapatite.
[0051] The concentration of the sodium dihydrogen phosphate aqueous solution is 15 g / L;
[0052] The particle size of the antimony trioxide is 1 μm;
[0053] The concentration of the calcium chloride aqueous solution is 15 g / L;
[0054] (2) Cross-linking: Add 13 mL of acetic acid and 970 mL of water to a reactor, control the stirring speed of the reactor to 30 rpm, stir at room temperature for 5 min, add 10 g of chitosan, stir for 15 min, add 100 g of antimony trioxide coated with hydroxyapatite, stir for 1 h, add 7 g of sodium alginate, stir for 1 h, add the contents of the reactor to a centrifuge, control the speed of the centrifuge to 4000 rpm, centrifuge for 10 min, add the obtained precipitate and 340 mL of water to a reactor, control the stirring speed of the reactor to 30 rpm, stir at room temperature for 10 min, add 300 mL of sodium tripolyphosphate aqueous solution dropwise, control the dropping speed to 15 mL / min, stir for 1.5 h after the addition is completed, add the contents of the reactor to a centrifuge, control the speed of the centrifuge to 4000 rpm, centrifuge for 9 min, wash the precipitate with water 3 times, and vacuum dry at 85 °C to obtain cross-linked antimony trioxide;
[0055] The weight average molecular weight of the chitosan is 50 kDa, and the degree of deacetylation is 90%;
[0056] The concentration of the sodium tripolyphosphate aqueous solution is 50 g / L;
[0057] (3) Primary hydrophobicization: 28 g of Tween 80 and 750 mL of water were added to a reactor, the stirring speed of the reactor was controlled to 30 rpm, and the mixture was stirred at room temperature for 15 min. 110 g of cross-linked antimony trioxide was added and stirred for 1.5 h. The contents of the reactor were added to a centrifuge, the speed of the centrifuge was controlled to 4000 rpm, and the mixture was centrifuged for 14 min. The precipitate was washed with water for 3 times, and vacuum dried at 100 °C to obtain a composite flame retardant.
[0058] 2. Preparation of composite adsorbent:
[0059] (1) Intercalation: 13 mL of acetic acid and 970 mL of water were added to a reactor, the stirring speed of the reactor was controlled to 30 rpm, and the mixture was stirred at room temperature for 5 min. 10 g of chitosan and 24 g of polyvinyl alcohol were added, and the mixture was stirred for 15 min. 30 g of hydrotalcite was added, the temperature of the reactor was controlled to 60 ° C, and the mixture was stirred for 5 h. The contents of the reactor were added to a centrifuge, the speed of the centrifuge was controlled to 8000 rpm, and the mixture was centrifuged for 10 min. The obtained precipitate and 250 mL of water were added to a reactor, the stirring speed of the reactor was controlled to 30 rpm, and the mixture was stirred at room temperature for 10 min. 140 mL of glutaraldehyde aqueous solution was added dropwise, and the dropping speed was controlled to 9 mL / min. After the addition was completed, the temperature of the reactor was controlled to 50 ° C, and the mixture was stirred for 3.5 h. The contents of the reactor were added to a centrifuge, the speed of the centrifuge was controlled to 8000 rpm, and the mixture was centrifuged for 10 min. The precipitate was washed with water for 3 times, and vacuum dried at 85 ° C to obtain the intercalated hydrotalcite.
[0060] The particle size of the hydrotalcite is 500 nm;
[0061] The weight average molecular weight of the chitosan is 50 kDa, and the degree of deacetylation is 90%;
[0062] The specification of the polyvinyl alcohol is polyvinyl alcohol 1788;
[0063] The concentration of the glutaraldehyde aqueous solution is 5wt%;
[0064] (2) Secondary hydrophobicization: 10 g of Tween 80 and 500 mL of water were added to the reactor, the stirring speed of the reactor was controlled to 30 rpm, and the mixture was stirred at room temperature for 15 min. 34 g of intercalated hydrotalcite was added and stirred for 1.5 h. The contents of the reactor were added to a centrifuge, the speed of the centrifuge was controlled to 8000 rpm, and the mixture was centrifuged for 14 min. The precipitate was washed with water for 3 times and dried under vacuum at 100 °C to obtain a composite adsorbent.
[0065] 3. Granulation: Add polystyrene, methyl octabromoether, composite flame retardant, composite adsorbent, antioxidant 168, zinc stearate and 3-aminopropyltriethoxysilane into a mixer in a mass ratio of 34:25:12:7:0.3:0.4:2 and mix well, then add into a twin-screw extruder for melt extrusion, control the temperature of zone 1 of the twin-screw extruder to 160°C, the temperature of zone 2 to 185°C, the temperature of zone 3 to 195°C, the temperature of zone 4 to 200°C, the temperature of zone 5 to 205°C, the temperature of zone 6 to 205°C and the temperature of the die head to 205°C to obtain XPS flame retardant masterbatch.
[0066] This embodiment also provides an XPS flame retardant masterbatch prepared by the aforementioned preparation method.
[0067] Example 2
[0068] A method for preparing XPS flame retardant masterbatch, specifically comprising:
[0069] 1. Preparation of composite flame retardant:
[0070] (1) Coating hydroxyapatite: 580 mL of water, 1750 mL of anhydrous ethanol and 35 g of urea were added to a reactor, the stirring speed of the reactor was controlled to 60 rpm, and the mixture was stirred at room temperature for 12 min. 590 mL of sodium dihydrogen phosphate aqueous solution was added, and the mixture was stirred for 8 min. 105 g of antimony trioxide was added, and the mixture was stirred for 15 min. 980 mL of calcium chloride aqueous solution was added, and the mixture was stirred for 12 min. Sodium hydroxide was added to adjust the pH to 12. After the reactor was sealed, the reactor was placed in an oven, the temperature of the oven was controlled to 85° C., and the mixture was allowed to stand for 31 h. The reactor was taken out, and the contents of the reactor were placed in a centrifuge, the speed of the centrifuge was controlled to 4500 rpm, and the mixture was centrifuged for 10 min. The precipitate was washed with water for 3 times, and vacuum dried at 85° C. to obtain antimony trioxide coated with hydroxyapatite.
[0071] The concentration of the sodium dihydrogen phosphate aqueous solution is 15 g / L;
[0072] The particle size of the antimony trioxide is 1 μm;
[0073] The concentration of the calcium chloride aqueous solution is 15 g / L;
[0074] (2) Cross-linking: Add 14 mL of acetic acid and 980 mL of water to a reactor, control the stirring speed of the reactor to 60 rpm, stir at room temperature for 8 min, add 10.5 g of chitosan, stir for 18 min, add 105 g of antimony trioxide coated with hydroxyapatite, stir for 1.5 h, add 7.5 g of sodium alginate, stir for 1.5 h, add the contents of the reactor to a centrifuge, control the speed of the centrifuge to 4500 rpm, centrifuge for 10 min, add the obtained precipitate and 350 mL of water to a reactor, control the stirring speed of the reactor to 60 rpm, stir at room temperature for 12 min, add 310 mL of sodium tripolyphosphate aqueous solution dropwise, control the dropping speed to 18 mL / min, stir for 1.5 h after the addition is completed, add the contents of the reactor to a centrifuge, control the speed of the centrifuge to 4500 rpm, centrifuge for 10 min, wash the precipitate with water 3 times, and vacuum dry at 90 °C to obtain cross-linked antimony trioxide;
[0075] The weight average molecular weight of the chitosan is 50 kDa, and the degree of deacetylation is 90%;
[0076] The concentration of the sodium tripolyphosphate aqueous solution is 50 g / L;
[0077] (3) Primary hydrophobicization: 29 g of Tween 80 and 780 mL of water were added to a reactor, the stirring speed of the reactor was controlled to 60 rpm, and the mixture was stirred at room temperature for 20 min. 115 g of cross-linked antimony trioxide was added and stirred for 1.5 h. The contents of the reactor were added to a centrifuge, the speed of the centrifuge was controlled to 4500 rpm, and the mixture was centrifuged for 15 min. The precipitate was washed with water for 3 times, and vacuum dried at 105 °C to obtain a composite flame retardant.
[0078] 2. Preparation of composite adsorbent:
[0079] (1) Intercalation: 14 mL of acetic acid and 980 mL of water were added to a reactor, the stirring speed of the reactor was controlled to 60 rpm, and the mixture was stirred at room temperature for 10 min. 10.5 g of chitosan and 24.5 g of polyvinyl alcohol were added, and the mixture was stirred for 20 min. 31 g of hydrotalcite was added, the temperature of the reactor was controlled to 62 °C, and the mixture was stirred for 5.5 h. The contents of the reactor were added to a centrifuge, the speed of the centrifuge was controlled to 8500 rpm, and the mixture was centrifuged for 11 min. The obtained precipitate and 255 mL of water were added to a reactor, the stirring speed of the reactor was controlled to 60 rpm, and the mixture was stirred at room temperature for 12 min. 145 mL of glutaraldehyde aqueous solution was added dropwise, and the dropping speed was controlled to 10 mL / min. After the addition was completed, the temperature of the reactor was controlled to 52 °C, and the mixture was stirred for 4 h. The contents of the reactor were added to a centrifuge, the speed of the centrifuge was controlled to 8500 rpm, and the mixture was centrifuged for 11 min. The precipitate was washed with water for 4 times, and vacuum dried at 90 °C to obtain the intercalated hydrotalcite.
[0080] The particle size of the hydrotalcite is 500 nm;
[0081] The weight average molecular weight of the chitosan is 50 kDa, and the degree of deacetylation is 90%;
[0082] The specification of the polyvinyl alcohol is polyvinyl alcohol 1788;
[0083] The concentration of the glutaraldehyde aqueous solution is 5wt%;
[0084] (2) Secondary hydrophobicization: 10.5 g of Tween 80 and 520 mL of water were added to the reactor, the stirring speed of the reactor was controlled to 60 rpm, and the mixture was stirred at room temperature for 20 min. 35 g of intercalated hydrotalcite was added and stirred for 1.5 h. The contents of the reactor were added to a centrifuge, the speed of the centrifuge was controlled to 8500 rpm, and the mixture was centrifuged for 15 min. The precipitate was washed with water for 3 times and dried under vacuum at 105 °C to obtain a composite adsorbent.
[0085] 3. Granulation: Add polystyrene, methyl octabromoether, composite flame retardant, composite adsorbent, antioxidant 168, zinc stearate and 3-aminopropyltriethoxysilane into a mixer in a mass ratio of 35:26:13:7.5:0.3:0.5:2.2 and mix well. Then add into a twin-screw extruder for melt extrusion. Control the temperature of the first zone of the twin-screw extruder to 165°C, the temperature of the second zone to 190°C, the temperature of the third zone to 200°C, the temperature of the fourth zone to 205°C, the temperature of the fifth zone to 210°C, the temperature of the sixth zone to 210°C and the temperature of the die head to 210°C to obtain XPS flame retardant masterbatch.
[0086] This embodiment also provides an XPS flame retardant masterbatch prepared by the aforementioned preparation method.
[0087] Example 3
[0088] A method for preparing XPS flame retardant masterbatch, specifically comprising:
[0089] 1. Preparation of composite flame retardant:
[0090] (1) Coating hydroxyapatite: add 600 mL of water, 1800 mL of anhydrous ethanol, and 36 g of urea to a reactor, control the stirring speed of the reactor to 60 rpm, stir at room temperature for 15 min, add 600 mL of sodium dihydrogen phosphate aqueous solution, stir for 10 min, add 110 g of antimony trioxide, stir for 20 min, add 1000 mL of calcium chloride aqueous solution, stir for 15 min, add sodium hydroxide to adjust the pH to 12, seal the reactor, add the reactor to an oven, control the temperature of the oven to 90°C, let it stand for 32 h, take out the reactor, add the materials in the reactor to a centrifuge, control the speed of the centrifuge to 5000 rpm, centrifuge for 11 min, wash the precipitate with water 4 times, and vacuum dry it at 90°C to obtain antimony trioxide coated with hydroxyapatite;
[0091] The concentration of the sodium dihydrogen phosphate aqueous solution is 15 g / L;
[0092] The particle size of the antimony trioxide is 1 μm;
[0093] The concentration of the calcium chloride aqueous solution is 15 g / L;
[0094] (2) Cross-linking: add 15 mL of acetic acid and 1000 mL of water to a reactor, control the stirring speed of the reactor to 60 rpm, stir at room temperature for 10 min, add 11 g of chitosan, stir for 20 min, add 110 g of antimony trioxide coated with hydroxyapatite, stir for 1.5 h, add 8 g of sodium alginate, stir for 1.5 h, add the contents of the reactor to a centrifuge, control the speed of the centrifuge to 5000 rpm, centrifuge for 11 min, add the obtained precipitate and 360 mL of water to a reactor, control the stirring speed of the reactor to 60 rpm, stir at room temperature for 15 min, add 320 mL of sodium tripolyphosphate aqueous solution dropwise, control the dropping speed to 20 mL / min, stir for 2 h after the addition is completed, add the contents of the reactor to a centrifuge, control the speed of the centrifuge to 5000 rpm, centrifuge for 10 min, wash the precipitate with water 4 times, and vacuum dry at 90 °C to obtain cross-linked antimony trioxide;
[0095] The weight average molecular weight of the chitosan is 50 kDa, and the degree of deacetylation is 90%;
[0096] The concentration of the sodium tripolyphosphate aqueous solution is 50 g / L;
[0097] (3) Primary hydrophobicization: 30 g of Tween 80 and 800 mL of water were added to a reactor, the stirring speed of the reactor was controlled to 60 rpm, and the mixture was stirred at room temperature for 20 min. 120 g of cross-linked antimony trioxide was added and stirred for 2 h. The contents of the reactor were added to a centrifuge, the speed of the centrifuge was controlled to 5000 rpm, and the mixture was centrifuged for 15 min. The precipitate was washed with water for 4 times, and vacuum dried at 105 °C to obtain a composite flame retardant.
[0098] 2. Preparation of composite adsorbent:
[0099] (1) Intercalation: 15 mL of acetic acid and 1000 mL of water were added to a reactor, the stirring speed of the reactor was controlled to 60 rpm, and the mixture was stirred at room temperature for 10 min. 11 g of chitosan and 25 g of polyvinyl alcohol were added, and the mixture was stirred for 20 min. 32 g of hydrotalcite was added, the temperature of the reactor was controlled to 65 ° C, and the mixture was stirred for 6 h. The contents of the reactor were added to a centrifuge, the speed of the centrifuge was controlled to 9000 rpm, and the mixture was centrifuged for 11 min. The obtained precipitate and 260 mL of water were added to a reactor, the stirring speed of the reactor was controlled to 60 rpm, and the mixture was stirred at room temperature for 15 min. 150 mL of glutaraldehyde aqueous solution was added dropwise, and the dropping speed was controlled to 10 mL / min. After the addition was completed, the temperature of the reactor was controlled to 55 ° C, and the mixture was stirred for 4 h. The contents of the reactor were added to a centrifuge, the speed of the centrifuge was controlled to 9000 rpm, and the mixture was centrifuged for 11 min. The precipitate was washed with water for 4 times, and vacuum dried at 90 ° C to obtain the intercalated hydrotalcite.
[0100] The particle size of the hydrotalcite is 500 nm;
[0101] The weight average molecular weight of the chitosan is 50 kDa, and the degree of deacetylation is 90%;
[0102] The specification of the polyvinyl alcohol is polyvinyl alcohol 1788;
[0103] The concentration of the glutaraldehyde aqueous solution is 5wt%;
[0104] (2) Secondary hydrophobicization: 11 g of Tween 80 and 550 mL of water were added to the reactor, the stirring speed of the reactor was controlled to 60 rpm, and the mixture was stirred at room temperature for 20 min. 37 g of intercalated hydrotalcite was added and stirred for 2 h. The contents of the reactor were added to a centrifuge, the speed of the centrifuge was controlled to 9000 rpm, and the mixture was centrifuged for 15 min. The precipitate was washed with water for 4 times and dried under vacuum at 105 °C to obtain a composite adsorbent.
[0105] 3. Granulation: Add polystyrene, methyl octabromoether, composite flame retardant, composite adsorbent, antioxidant 168, zinc stearate and 3-aminopropyltriethoxysilane into a mixer in a mass ratio of 35:27:14:8:0.4:0.5:2.3, mix well, add into a twin-screw extruder for melt extrusion, control the temperature of the first zone of the twin-screw extruder to 165°C, the temperature of the second zone to 190°C, the temperature of the third zone to 200°C, the temperature of the fourth zone to 205°C, the temperature of the fifth zone to 210°C, the temperature of the sixth zone to 210°C, and the temperature of the die head to 210°C to obtain XPS flame retardant masterbatch.
[0106] This embodiment also provides an XPS flame retardant masterbatch prepared by the aforementioned preparation method.
[0107] Comparative Example 1
[0108] On the basis of the preparation method of XPS flame retardant masterbatch in Example 2, the step of preparing the composite flame retardant in step 1 is omitted, and in the granulation step in step 3, antimony trioxide with a particle size of 1 μm is used as an equal mass to replace the composite flame retardant;
[0109] This comparative example also provides an XPS flame retardant masterbatch prepared by the aforementioned preparation method.
[0110] Comparative Example 2
[0111] On the basis of the preparation method of the XPS flame retardant masterbatch of Example 2, the second step of preparing the composite adsorbent is omitted, and in the third step of granulation, hydrotalcite powder with a particle size of 200 nm is used as the composite adsorbent instead of the mass;
[0112] This comparative example also provides an XPS flame retardant masterbatch prepared by the aforementioned preparation method.
[0113] Application Example 1
[0114] The XPS flame retardant masterbatch prepared in Example 1 was applied to the preparation of XPS material, specifically:
[0115] Polystyrene, the XPS flame retardant masterbatch prepared in Example 1, and a foaming agent were added to a mixer in a mass ratio of 88:6:6, and mixed evenly, and then added to a twin-screw extruder for extrusion and foaming to obtain an XPS material;
[0116] The foaming agent consists of 1,1,1,2-tetrafluoroethane and dimethyl ether, wherein the mass ratio of 1,1,1,2-tetrafluoroethane to dimethyl ether is 1:1.
[0117] Application Example 2
[0118] The XPS flame retardant masterbatch prepared in Example 2 was applied to the preparation of XPS material, specifically:
[0119] Polystyrene, the XPS flame retardant masterbatch prepared in Example 2, and a foaming agent were added to a mixer at a mass ratio of 88:6:6, and mixed evenly, and then added to a twin-screw extruder for extrusion and foaming to obtain an XPS material;
[0120] The foaming agent consists of 1,1,1,2-tetrafluoroethane and dimethyl ether, wherein the mass ratio of 1,1,1,2-tetrafluoroethane to dimethyl ether is 1:1.
[0121] Application Example 3
[0122] The XPS flame retardant masterbatch prepared in Example 3 was applied to the preparation of XPS material, specifically:
[0123] Polystyrene, the XPS flame retardant masterbatch prepared in Example 3, and a foaming agent were added to a mixer in a mass ratio of 88:6:6, and mixed evenly, and then added to a twin-screw extruder for extrusion and foaming to obtain an XPS material;
[0124] The foaming agent consists of 1,1,1,2-tetrafluoroethane and dimethyl ether, wherein the mass ratio of 1,1,1,2-tetrafluoroethane to dimethyl ether is 1:1.
[0125] Application Example 4
[0126] The XPS flame retardant masterbatch prepared in Comparative Example 1 was applied to the preparation of XPS material, specifically:
[0127] Polystyrene, the XPS flame retardant masterbatch prepared in Comparative Example 1, and a foaming agent were added to a mixer at a mass ratio of 88:6:6, mixed evenly, and then added to a twin-screw extruder for extrusion and foaming to obtain an XPS material;
[0128] The foaming agent consists of 1,1,1,2-tetrafluoroethane and dimethyl ether, wherein the mass ratio of 1,1,1,2-tetrafluoroethane to dimethyl ether is 1:1.
[0129] Application Example 5
[0130] The XPS flame retardant masterbatch prepared in Comparative Example 2 was applied to the preparation of XPS material, specifically:
[0131] Polystyrene, the XPS flame retardant masterbatch prepared in Comparative Example 2, and a foaming agent were added to a mixer at a mass ratio of 88:6:6, mixed evenly, and then added to a twin-screw extruder for extrusion and foaming to obtain an XPS material;
[0132] The foaming agent consists of 1,1,1,2-tetrafluoroethane and dimethyl ether, wherein the mass ratio of 1,1,1,2-tetrafluoroethane to dimethyl ether is 1:1.
[0133] Test Example 1
[0134] The combustion performance, oxygen index, smoke density level, water absorption (immersion in water for 96 hours), and thermal conductivity of the XPS materials prepared according to Examples 1-5 were tested. The test results are as follows:
[0135]
[0136] Test Example 2
[0137] In the third step of granulation in Example 1-3 and Comparative Example 1-2, the hydrogen bromide gas concentration at the head of the twin screw extruder was detected when the twin screw extruder was used for melting and extrusion. The detection was performed every 5 minutes for 20 consecutive times, and the maximum hydrogen bromide gas concentration was recorded. The recorded results are as follows:
[0138]
[0139] Test Example 3
[0140] The compressive strength of the XPS materials prepared according to Example 1-5 was tested, and the test results are as follows:
[0141]
[0142] The XPS material prepared in Application Example 1-5 was added into a xenon lamp aging box, and the atmosphere of the xenon lamp aging box was controlled to be an air atmosphere, the temperature was 65°C, the power was 1.8kW, and the irradiation was continued for 15 days. Then the compressive strength was tested, and the compressive strength decrease rate was calculated. The calculation results are as follows:
[0143]
[0144] It can be seen from the results of test examples 1-3 that the maximum hydrogen bromide gas concentration generated when preparing XPS flame retardant masterbatch in comparative example 1-2 is greater than the maximum hydrogen bromide gas concentration generated when preparing XPS flame retardant masterbatch in example 2, and the oxygen index, smoke density level, water absorption rate, thermal conductivity, compressive strength, and aging resistance of the XPS material prepared from the XPS flame retardant masterbatch of comparative example 1-2 are all worse than those of the XPS material prepared from the XPS flame retardant masterbatch of example 2. Combining the technical solutions of example 2 and comparative example 1-2, it is shown that the effect of using antimony trioxide alone as a flame retardant or using hydrotalcite alone as a hydrogen bromide gas adsorbent is worse than that of a composite flame retardant or a composite adsorbent.
[0145] Unless otherwise specified, all percentages used in the present invention are by mass.
[0146] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing XPS flame retardant masterbatch, characterized in that: The method comprises the following steps: preparing a composite flame retardant, preparing a composite adsorbent, and granulating; The preparation of the composite flame retardant comprises the following steps: preparing antimony trioxide coated with hydroxyapatite, cross-linking, and primary hydrophobization; The preparation process of the antimony trioxide coated hydroxyapatite is as follows: adding water, anhydrous ethanol and urea into a reactor, controlling the stirring speed of the reactor to 30-60 rpm, stirring at room temperature for 10-15 minutes, adding sodium dihydrogen phosphate aqueous solution, stirring for 5-10 minutes, adding antimony trioxide, stirring for 10-20 minutes, adding calcium chloride aqueous solution, stirring for 10-15 minutes, adding sodium hydroxide to adjust the pH to 11.5-12, sealing the reactor, adding the reactor into an oven, controlling the temperature of the oven to 80-90° C., standing for 30-32 hours, taking out the reactor, adding the materials in the reactor into a centrifuge, controlling the speed of the centrifuge to 4000-5000 rpm, centrifuging for 10-11 minutes, washing the precipitate with water for 3-4 times, and vacuum drying at 85-90° C. to obtain antimony trioxide coated hydroxyapatite; The cross-linking comprises: mixing glacial acetic acid and the first portion of water, stirring at room temperature, adding chitosan, stirring, adding antimony trioxide coated with hydroxyapatite, stirring, adding sodium alginate, stirring, centrifuging, mixing the obtained precipitate with the second portion of water, stirring at room temperature, dripping sodium tripolyphosphate aqueous solution, stirring after dripping, centrifuging, taking the precipitate, washing, and vacuum drying to obtain cross-linked antimony trioxide; The primary hydrophobization comprises: mixing Tween 80 and water, stirring at room temperature, adding cross-linked antimony trioxide, stirring, centrifuging, taking a precipitate, washing, and vacuum drying to obtain a composite flame retardant; The preparation of the composite adsorbent comprises the following steps: intercalation, secondary hydrophobization; The intercalation comprises: mixing glacial acetic acid and the first portion of water, stirring at room temperature, adding chitosan and polyvinyl alcohol, stirring, adding hydrotalcite, stirring at 60-65° C., centrifuging, mixing the obtained precipitate with the second portion of water, stirring at room temperature, dropping glutaraldehyde aqueous solution, stirring at 50-55° C. after the dropping is completed, centrifuging, taking the precipitate, washing, and vacuum drying to obtain the intercalated hydrotalcite; The secondary hydrophobization comprises: mixing Tween 80 and water, stirring at room temperature, adding the intercalated hydrotalcite, stirring, centrifuging, taking the precipitate, washing, and vacuum drying to obtain a composite adsorbent; The granulation comprises: adding polystyrene, methyl octabromoether, composite flame retardant, composite adsorbent, antioxidant 168, zinc stearate and 3-aminopropyl triethoxysilane into a mixer and mixing them evenly, and then adding them into a twin-screw extruder for melt extrusion to obtain XPS flame retardant masterbatch; In the granulation, the mass ratio of polystyrene, methyl octabromoether, composite flame retardant, composite adsorbent, antioxidant 168, zinc stearate and 3-aminopropyltriethoxysilane is 34-35:25-27:12-14:7-8:0.3-0.4:0.4-0.5:2-2.
3.
2. The method for preparing XPS flame retardant masterbatch according to claim 1, characterized in that: In the preparation of antimony trioxide coated with hydroxyapatite, the usage ratio of water, anhydrous ethanol, urea, sodium dihydrogen phosphate aqueous solution, antimony trioxide, and calcium chloride aqueous solution is 570-600mL: 1700-1800mL: 34-36g: 580-600mL: 100-110g: 960-1000mL; In the preparation of antimony trioxide coated with hydroxyapatite, the concentration of the sodium dihydrogen phosphate aqueous solution is 15 g / L; The particle size of the antimony trioxide is 1 μm; The concentration of the calcium chloride aqueous solution is 15 g / L.
3. The method for preparing XPS flame retardant masterbatch according to claim 1, characterized in that: In the cross-linking, the usage ratio of glacial acetic acid, the first portion of water, chitosan, antimony trioxide coated with hydroxyapatite, sodium alginate, the second portion of water, and sodium tripolyphosphate aqueous solution is 13-15mL:970-1000mL:10-11g:100-110g:7-8g:340-360mL:300-320mL; In the cross-linking, the weight average molecular weight of the chitosan is 50 kDa, and the degree of deacetylation is 90%; The concentration of the sodium tripolyphosphate aqueous solution is 50 g / L; The dropping speed of the sodium tripolyphosphate aqueous solution is 15-20 mL / min.
4. The method for preparing XPS flame retardant masterbatch according to claim 1, characterized in that: In the primary hydrophobization, the usage ratio of Tween 80, water, and cross-linked antimony trioxide is 28-30 g:750-800 mL:110-120 g.
5. The method for preparing XPS flame retardant masterbatch according to claim 1, characterized in that: In the intercalation, the usage ratio of glacial acetic acid, the first portion of water, chitosan, polyvinyl alcohol, hydrotalcite, the second portion of water, and glutaraldehyde aqueous solution is 13-15 mL: 970-1000 mL: 10-11 g: 24-25 g: 30-32 g: 250-260 mL: 140-150 mL; In the intercalation layer, the particle size of the hydrotalcite powder is 500 nm; The weight average molecular weight of the chitosan is 50 kDa, and the degree of deacetylation is 90%; The specification of the polyvinyl alcohol is polyvinyl alcohol 1788; The concentration of the glutaraldehyde aqueous solution is 5wt%; The dropping speed of the glutaraldehyde aqueous solution is 9-10 mL / min.
6. The method for preparing XPS flame retardant masterbatch according to claim 1, characterized in that: In the secondary hydrophobization, the usage ratio of Tween 80, water, and intercalated hydrotalcite is 10-11 g: 500-550 mL: 34-37 g.
7. The method for preparing XPS flame retardant masterbatch according to claim 1, characterized in that: In the granulation, during melt extrusion, the temperature of zone 1 of the twin-screw extruder is 160-165°C, the temperature of zone 2 is 185-190°C, the temperature of zone 3 is 195-200°C, the temperature of zone 4 is 200-205°C, the temperature of zone 5 is 205-210°C, the temperature of zone 6 is 205-210°C, and the temperature of the die head is 205-210°C.
8. An XPS flame retardant masterbatch prepared by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
An XPS flame retardant masterbatch, its preparation and application
CN114573920B
A brominated flame retardant reinforced nylon material and preparation method thereof
CN116376274B
XPS flame-retardant masterbatch and preparation method thereof
CN109503968A
Halogen-free flame-retardant polystyrene master batch and preparation method thereof
CN110922691A